2018
DOI: 10.1200/jco.2018.78.3183
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Tolerability of First-Line Cetuximab Plus Leucovorin, Fluorouracil, and Oxaliplatin (FOLFOX-4) Versus FOLFOX-4 in Patients With RAS Wild-Type Metastatic Colorectal Cancer: The Open-Label, Randomized, Phase III TAILOR Trial

Abstract: Purpose Cetuximab in combination with chemotherapy is a standard-of-care first-line treatment regimen for patients with RAS wild-type (wt) metastatic colorectal cancer (mCRC); however, the efficacy of cetuximab plus leucovorin, fluorouracil, and oxaliplatin (FOLFOX) has never before been proven in a controlled and randomized phase III trial. To our knowledge, the TAILOR trial ( ClinicalTrials.gov identifier: NCT01228734) is the first randomized, multicenter, phase III study of the addition of cetuximab to firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
134
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 189 publications
(138 citation statements)
references
References 34 publications
3
134
0
1
Order By: Relevance
“…The benefit from cetuximab was limited to left-sided tumors, which were also associated with a trial randomized mCRC patients to receive FOLFOX with or with panitumumab. 52 The benefit from panitumumab was limited to RAS 50 The study recapitulated the prior findings from CRYSTAL and PRIME, confirming a significant improvement in RR, PFS, and OS in left-sided RAS wild-type patients ( Table 5). (Table 5).…”
Section: First Line Anti-egfr Therapysupporting
confidence: 74%
See 3 more Smart Citations
“…The benefit from cetuximab was limited to left-sided tumors, which were also associated with a trial randomized mCRC patients to receive FOLFOX with or with panitumumab. 52 The benefit from panitumumab was limited to RAS 50 The study recapitulated the prior findings from CRYSTAL and PRIME, confirming a significant improvement in RR, PFS, and OS in left-sided RAS wild-type patients ( Table 5). (Table 5).…”
Section: First Line Anti-egfr Therapysupporting
confidence: 74%
“…The benefit from cetuximab was limited to left‐sided tumors, which were also associated with a favorable outcome in comparison to right‐sided tumors. The combination of FOLFOX with or without anti‐EGFR therapy was evaluated in two randomized phase III clinical trials . The PRIME trial randomized mCRC patients to receive FOLFOX with or with panitumumab .…”
Section: Biological and Targeted Therapy In Mcrcmentioning
confidence: 99%
See 2 more Smart Citations
“…The process of the literature selection and reasons for study exclusion are shown in Figure . We identified 3906 potentially relevant records through electronic search and 18 RCTs were ultimately included in this review after removal of duplicate publications and ineligible studies.…”
Section: Resultsmentioning
confidence: 99%